A RESEARCH ON ARTIFICIAL INTELLIGENCE AND ETHICS - KÜÇÜKVARDAR, Mert; ASLAN, Alaattin; BAYRAKCI, Serkan (Atlas Journal, 2020)
The speed of technological developments has reached dimensions that will lead to social problems. This situation indicates that conscientious structures should be prioritized more than the weight of legal regulations. Especially moral-ethical behavior style was handled in parallel with technological developments. This raises many problems that need to be reinterpreted. Problems are growing with the impact of studies challenging the moral-ethical field, including artificial intelligence studies, biotechnological developments, genetic engineering. The problems mostly focus on the following questions: Do the machines have a morality? Would it be ethical and moral to arrest them if there was a machine intelligence that could detect possible crimes and criminals before they were committed? Should biotechnology and genetic technology only be used for medical purposes or to make healthy people stronger and smarter? Increased connectivity and symbiotic interaction between people and smart machines is a serious area of discussion for morality and contemporary ethics. 2 In this study, moral challenges were examined by literature review and the technology-ethics dilemma was examined through case studies. As a result, technological advances are progressing very quickly, but moral principles cannot keep up with it. Therefore, it seems that a new technology-based moral principles and a different sociological understanding are needed